Generation of bovine iPSCs from fetal fibroblasts for in vitro myogenesis and cultured meat - Recchia, Kaiana; Wathikthinnakon, Methi; Bressan, Fabiana Fernandes; Freude, Kristine (Frontiers in Nutrition, 2025)
IntroductionEmerging biotechnologies are increasingly being explored for food production, including the development of cell-cultivated meat. Conventional approaches typically rely on satellite cell (SC) biopsies, which present challenges in scalability. Bovine induced pluripotent stem cells (biPSCs) represent a promising alternative due to their capacity for self-renewal and developmental plasticity.MethodsThis study utilized both lentiviral (integrating) and episomal (non-integrating) reprogramming strategies to generate biPSCs suitable for myogenic differentiation. Bovine fetal fibroblasts (bFFs) were reprogrammed using episomal vectors pMaster K and pCXB-EBNA1, leading to the emergence of putative iPSC colonies 13 days post-nucleofection. A clonal line, bFF-iPSCs pMK, was selected for further analysis.ResultsThe bFF-iPSCs pMK line expressed key pluripotency markers including alkaline phosphatase (AP), OCT4, SOX2, and NANOG, and was stably maintained for over 33 passages, although episomal plasmids remained detectable. in vitro myogenic differentiation was assessed by comparing this line to a previously established lentiviral reprogrammed line (bFF-iPSCs mOSKM). Both lines exhibited downregulation of pluripotency markers and upregulation of the early myogenic marker PAX3. By day 30, the bFF-iPSCs pMK line formed elongated, multinucleated cells characteristic of myotubes and displayed a corresponding gene expression profile.DiscussionThese results provide new insights into bovine in vitro myogenesis and its application in cultured meat production. While promising, the study also highlights the difficulty in achieving complete myogenic differentiation, indicating a need for further optimization of differentiation protocols.